Evaluation on the Mechanical Properties of Concrete Using Clay Brick as Sand Substitution - Balqis Ismail, Herda; Mahmud, Khairulanas; ., Daniel; Hayati Anuar, Nur; Syafina Azman, Nur; Afiq Abd Wahab, Mohd; Johan Mohamed Ibrahim, Mohd; Shahidah Saripudin, Siti; Muizzah Nawi, Nur; Hazizi Jamal, Mohammad (International Journal of Engineering and Technology, 2018)
This paper investigates the mechanical properties of Clay Brick Powder Composites in the concrete design mix proportion in terms of compressive strength behavior. The Clay brick powder employed in this study is from the recycle brick waste of demolished house. The brick is being grinded by using Los Angeles Abrasion Machine. Three samples are being produced which contain the replacement of sand by substituting the first sample with 15% of brick powder, second sample with 20% of brick powder and third sample with 25% of brick powder. All the samples have been tested for compressive strength by using the Compression Testing Machine. The results show that the optimum proportion of clay brick powder as a fine aggregate replacement is 15 %, which recorded to have 58 MPa that is the highest compressive strength at the age of 28 days compare to the other proportion. Overall, in between of 15-25% of fine aggregate replacement, the strength can reach the highest performance at about 45-58 MPa of the compression. This can be concluded that the concrete clay brick has good and applicable compressive strength plus lighter than the normal concrete. This makes the concrete as one of the eco-friendly construction material.Â Â